2017
DOI: 10.3389/fpsyg.2017.01501
|View full text |Cite
|
Sign up to set email alerts
|

Contour Integration in Dynamic Scenes: Impaired Detection Performance in Extended Presentations

Abstract: Since scenes in nature are highly dynamic, perception requires an on-going and robust integration of local information into global representations. In vision, contour integration (CI) is one of these tasks, and it is performed by our brain in a seemingly effortless manner. Following the rule of good continuation, oriented line segments are linked into contour percepts, thus supporting important visual computations such as the detection of object boundaries. This process has been studied almost exclusively usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…It is also possible that the focus on individual features that was trained in the change-detection task was inappropriate to lead to positive changes in integrating multiple features into wholes as needed in the contour integration task. Finally, our contour integration task allowed participants to respond within a relatively wide time window which further increases task difficulty, as it has been shown that the ability to detect a contour worsens with prolonged presentation 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the focus on individual features that was trained in the change-detection task was inappropriate to lead to positive changes in integrating multiple features into wholes as needed in the contour integration task. Finally, our contour integration task allowed participants to respond within a relatively wide time window which further increases task difficulty, as it has been shown that the ability to detect a contour worsens with prolonged presentation 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Contour integration is based on the Gestalt law of “good continuation”, referring to the preference in viewing an object as something that is smooth and continuous rather than something that is abrupt and disconnected through the integration of local elements to form a global contour 31 , 32 . Contour integration is a special case of visual grouping, which refers to the idea that the visual system tends to group elements into visual wholes through simple rules 33 .…”
Section: Introductionmentioning
confidence: 99%
“…In modern science, researchers found that oriented lines or objects contribute significantly to visual perceptions [ 7 , 8 ]. Under certain circumstances, the lines and line orientations in an image affect people’s perception, behavior, and even decision-making [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%